EDUKASI PERPAJAKAN GUNA PENINGKATAN KONTRIBUSI PENDAPATAN NEGARA - Maharani, Destin Alfianika; Arofah, Anastasia Anggarkusuma; Renovriska, Melia Dwi; Fitriyanti, Fitriyanti; Astuti, Tri (ABDI MAKARTI, 2025)
This community service program aimed to enhance tax awareness and understanding among micro, small, and medium enterprises (MSMEs) in Blambangan Village, Banjarnegara. Despite increased awareness following training, low tax literacy remains a major challenge. Many participants were still unfamiliar with tax regulations, calculation procedures, and administrative processes, including the synchronization of their Taxpayer Identification Number (NPWP) with their national ID number (NIK). The program was carried out through planning, implementation, and evaluation stages. Educational materials included general tax provisions, applicable tax rates, everyday tax practices, and fraud prevention. Results showed improved participant knowledge and awareness. However, continuous educational efforts are needed to ensure compliance and prevent potential administrative sanctions. Sustainable tax education—delivered in a practical and contextual manner—is essential for building a tax-compliant culture, especially in rural and developing communities. This program also supports the national goal of increasing state revenue through improved voluntary compliance among taxpayers.